(untitled) (Prostor, 2023)
This study examines and contrasts the implementation and results of smart initiatives across four domains - smart people, smart economy, smart environment, and information and communication technologies (ICT) - in four large-sized-smart cities: London, Paris, Barcelona, and Milan. By investigating these domains, the study intends to assess the effectiveness of smart city strategies. It examines how technology and data-driven approaches have been implemented to enhance citizen participation, promote environmental sustainability, and stimulate economic growth. This research contributes to an in-depth comprehension of the many facets of smart cities and their potential to transform urban environments.